RECOVERY OF POLYHYDROXYALKANOATES (PHAs) FROM BACTERIAL CELLS USING ENZYMATIC PROCESS - S. Marsudi (Reaktor, 2006)
Polyhydroxyalkanoates (PHAs) are intracellular material accumulated by several bacteria. Commercial production of PHAs faces the issue of high production cost especially substrate cost and recovery/separation cost. An alternative to reduce the production cost is to use enzyme and or chemical to recover PHAs from bacterial cells. Recovery of PHAs from bacterial cells was done using enzyme, chemical, and a mixture of enzyme and chemical. Enzyme (s) and or chemical(s) were added into culture broth to disrupt cells after adjusting pH and temperature of the culture broth. Treatment by adding enzyme or chemical only into culture broth showed a low level of PHAs recovered from bacterial cells. Treatment by adding a mixture of enzymes and chemicals showed the best result among 22 examined combinations, i.e. a mixture of EDTA, lisozyme, papain enzyme, and SDS. This combination gave a PHA recovery of 65 % w/w.